Determinants of changes in women's and men's eating behavior across the transition to parenthood: a focus group study - Vickà Versele; F. Marijn Stok; Dirk Aerenhouts; Benedicte Deforche; Annick Bogaerts; Roland Devlieger; Peter Clarys; Tom Deliens (BMC, 2021)
Abstract Background During the pregnancy and postpartum period, both women and men experience physiological and psychological changes, which may negatively impact their eating behavior. A clear understanding of determinants of changes in eating behavior during this period is needed to facilitate the development of targeted family-based interventions countering unfavorable dietary changes during this critical life period. Methods Thirteen focus group discussions targeting determinants of changes in eating behavior during pregnancy and postpartum were conducted, involving a total of 74 expecting and first-time parents. A semi-structured question guide was used to facilitate the discussions. An inductive thematic approach was used to derive main and sub-categories of determinants from the data. The Determinants of Nutrition and Eating (DONE)-framework was employed to systematically organize and label the categories and determinants. Results Two frameworks were developed; one for the pregnancy and one for the postpartum period, comprising determinants of changes in eating behavior in both women and men. Three main levels of determinants were identified: (1) the individual level, including psychological (e.g., 'health consciousness'), situational (e.g., 'effort and convenience') and biological (e.g., 'discomfort'); (2) the interpersonal level (e.g., 'social influence') and (3) the environmental level, including micro- and meso/macro (e.g., 'home/environment food availability'). Determinants acting as barriers (e.g., 'time constraints') or facilitators (e.g., 'being a role model') were identified. Many determinants were mentioned during both (e.g., 'food knowledge') or just one investigated period (e.g., 'physiological changes' during pregnancy, 'influence of the baby' postpartum). Finally, some were described by both parents (e.g., 'self-regulation'), whereas others were mentioned by women (e.g., '(perceived) food safety') or men (e.g., 'other priorities') only. Conclusion The developed frameworks set the foundation for the development of future family-based interventions and may be used already by healthcare providers to provide dietary guidance and support for women and men transitioning into parenthood. A focus on the interplay of individual factors at the biological and psychological level together with situational difficulties during pregnancy is recommended. Postpartum, focus should go to support first-time parents to obtain balance of both maintaining one's own health and taking care of the baby, on improving self-regulation skills, and on coping with related situational constraints.